2022
DOI: 10.1097/hrp.0000000000000329
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Symptoms Across the Menstrual Cycle in Adult Women: A Comprehensive Review

Abstract: Learning objective After participating in this activity, learners should be better able to: • Discuss and outline the general and overlapping effects of the menstrual cycle on women’s mental health Abstract A growing body of research demonstrates menstrual cycle–dependent fluctuations in psychiatric symptoms; these fluctuations can therefore be considered as prevalent phenomena. Possible mechanisms underlying these fluctuations posit behavioral, psychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 234 publications
(493 reference statements)
1
43
0
5
Order By: Relevance
“…The irregularity of menstrual cycle in WWE could be associated with the decrease of luteal phase. This phenomenon was also seen in depression and anxiety ( 21 ). The correlation of epilepsy with menstrual disorders is thought to be due to the effect of epilepsy itself or an adverse effect of ASMs (clonazepam) on the neuroendocrine regulation of the menstrual cycle ( 7 , 22 ).…”
Section: Discussionmentioning
confidence: 69%
“…The irregularity of menstrual cycle in WWE could be associated with the decrease of luteal phase. This phenomenon was also seen in depression and anxiety ( 21 ). The correlation of epilepsy with menstrual disorders is thought to be due to the effect of epilepsy itself or an adverse effect of ASMs (clonazepam) on the neuroendocrine regulation of the menstrual cycle ( 7 , 22 ).…”
Section: Discussionmentioning
confidence: 69%
“…For example, many women experience physical discomfort (e.g. dysmenorrhoea, breast tenderness, joint pain) around the time of menstruation, along with negative emotions such as anxiety and depression 17,18 . Previous reviews by our colleagues suggest that disgust, as a neglected negative emotion, is implied in a broad range of psychopathological conditions 19,20 and is associated with hormonal uctuations during the menstrual cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The severity of these physical and mental symptoms can limit daily activity and can lead to a wide range of mental health concerns. 22 In a study on the relationship between women using oral contraceptive pills (OCPs) and the prevalence of symptoms, researchers found that those using OCPs reported less mastalgia, cramping, hair loss, acne, nervousness, and mood swings, relative to those not using hormonal contraception. 23 Research shows that hormonal IUDs can reduce the loss of blood and related problems at a higher rate than OCPs.…”
Section: Hormonal Birth Control Used To Reduce Menstrual Painmentioning
confidence: 99%